Illocutionary Speech Acts in An-Nabiy (The Prophet) by Kahlil Gibran: A Pragmatic Study - Novaldy Ramadhan Hermawan; Mawardi; Ihin Solihin (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to identify and analyze the types and functions of illocutionary speech acts in An-Nabiy by Kahlil Gibran, with a focus on how language is used to construct philosophical meaning and influence readers’ perspectives. The method employed is a descriptive qualitative approach with a pragmatic analysis technique, particularly speech act theory, through data collection in the form of textual excerpts, classification of illocutionary types, and interpretation of context and pragmatic force. The results show that the utterances in the text are dominated by assertive and directive speech acts. Assertive speech acts function to state, affirm, and challenge social beliefs through reflective and philosophical statements, while directive speech acts function to provide guidance and advice that encourage changes in attitude and awareness. These two types of speech acts work complementarily, where assertives build cognitive understanding, while directives guide actions and foster wiser attitudes. The findings indicate that language in the work is not only communicative but also transformative, as it is capable of shaping awareness, values, and readers’ perspectives on various aspects of life.